DEVELOPMENT OF EMPLOYEES’ SAFETY BEHAVIOR MANAGEMENT MODEL IN DOWNSTREAM OIL AND GAS COMPANIES OF MALAYSIA - ABD LATIFF KHAN, NOR HAFIZAH (2019)
Downstream oil and gas industry is largely associated with processes involving hazardous and flammable compounds, and chemical reactions that inherit high risks. The main purpose of this study was to develop a safety behavior management model in downstream oil and gas companies of Malaysia focusing for employees in the industry.